Effect of Behavioral Activation for Women with Postnatal Depression: A Systematic Review and Meta-Analysis - Engida Yisma; Sandra Walsh; Mary Steen; Richard Gray; Shaun Dennis; Marianne Gillam; Nayana Parange; Martin Jones (MDPI AG, 2024)
Evidence shows that behavioral activation (BA), a simple form of psychological therapy, is as effective as the more complex psychological therapy-cognitive behavioral therapy (CBT)-in treating general depression. However, it remains unclear whether BA when compared with treatment-as-usual (TAU) has greater contributions in reducing postnatal depression. This systematic review compared the effect of BA versus TAU in reducing depression symptoms among postnatal women. Five databases (MEDLINE, Embase, Emcare, Cochrane Library, and PsycINFO) were searched. Risk of bias was assessed using the Cochrane Collaboration's 'risk-of-bias 2 tool'. A random-effects meta-analysis was conducted to examine the effect of BA on postnatal depression. Of 2844 initial studies, only two randomized control trials (RCTs) met the inclusion criteria. The overall quality of evidence of these two RCTs was low. When compared to TAU, meta-analysis showed that BA was associated with reduced depression symptoms in postnatal women (standard mean difference −0.56; 95% confidence interval −0.76 to −0.37). This review suggests that BA might be more effective than TAU for alleviating postnatal depression. However, due to concerns about evidence quality, these findings should be interpreted cautiously.